2017
DOI: 10.18632/oncotarget.23419
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic predictors of pathological complete response to neoadjuvant chemoradiotherapy in locally advanced rectal cancer

Abstract: PurposeTo evaluate the value of morphological parameters that can be obtained conveniently by MRI for predicting pathologically complete response (pCR) in patients with rectal cancer.Materials and MethodsA cohort of 101 patients was examined using MRI before and after Neoadjuvant chemoradiotherapy (nCRT). Morphological parameters including maximum tumor area (MTA), maximum tumor length (MTL) and maximum tumor thickness (MTT), as well as cylindrical approximated tumor volume (CATV), distance to anal verge (DTA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Currently, there are very few researches that have described MRI parameters of post-ICT ∆TL for predicting a CR. The smaller post-nCRT tumor length predicted an increased pCR rate in the previous studies (20,26,27). FOWARC analyzed MRI images of 403 patients and found that baseline TL was a signi cant factor for predicting pCR probability and patients with TL (> 3 cm) may have a lower pCR probability (28).…”
Section: Discussionmentioning
confidence: 81%
“…Currently, there are very few researches that have described MRI parameters of post-ICT ∆TL for predicting a CR. The smaller post-nCRT tumor length predicted an increased pCR rate in the previous studies (20,26,27). FOWARC analyzed MRI images of 403 patients and found that baseline TL was a signi cant factor for predicting pCR probability and patients with TL (> 3 cm) may have a lower pCR probability (28).…”
Section: Discussionmentioning
confidence: 81%
“…MRI is currently an important method for preoperative staging of colorectal cancer [ 18 20 ]. It has high accuracy in the location and diagnosis of tumors, judgment of tumor infiltration depth, and determination of resection range.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cancer accounts for one-third of all colorectal cancers and approximately 39,220 new cases of rectal cancer with an estimated 5-year overall survival rate of 65% occur each year [1][2][3][4][5]. Nowadays, nCRT followed by surgical resection is the standard treatment, which is widely used for treatment of locally advanced (cT3, 4 and/or N+) rectal cancer (LARC) [6,7]. Prediction of response to treatment has a significant role in selection of treatment approach.…”
Section: Introductionmentioning
confidence: 99%